Relationship selling : managing human connections as sales assets / Jim Cathcart, Victor Antonio. - Cathcart, Jim, 1946-; Antonio, Victor (Booklogix, 2024)
Relationships should be considered as Assets and managed accordingly. When you establish a connection with someone, sustain it and become their preferred provider. All businesses reach out to make contact and get a sale, but only the best treat them as treasured friends. Those businesses are rewarded with a lifetime of sales that come more easily with every passing year. Learn the 8 core competencies to become a true relationship salesperson.